Participant views on involvement in a trial of social recovery cognitive–behavioural therapy. (February 2015) - Notley, Caitlin; Christopher, Rose; Hodgekins, Joanne; Byrne, Rory; French, Paul; Fowler, David
Abstract : Background: The PRODIGY trial (Prevention of long term social disability amongst young people with emerging psychological difficulties, ISRCTN47998710) is a pilot trial of social recovery cognitive–behavioural therapy (SRCBT). Aims: The PRODIGY qualitative substudy aimed to (a) explore individual experiences of participating in the pilot randomised, controlled trial (recruitment, randomisation, assessment) and initial views of therapy, and (b) to explore perceived benefits of taking part in research v. ethical concerns and potential risks. Method: Qualitative investigation using semi-structured interviews with thematic analysis. Results: Analysis revealed participant experiences around the key themes of acceptability, disclosure, practicalities, altruism and engagement. Conclusions: Participants in both trial arms perceived themselves as gaining benefits from being involved in the study, above and beyond the intervention. This has implications for the design of future research and services for this client group, highlighting the importance of being flexible and an individualised approach as key engagement tools.